Evaluasi Model Komunikasi Islam dalam Upaya Stop PMO: Evaluation of Islamic Communication Models in the Effort to Stop PMO - Zein, Achyar (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This study aims to evaluate the effectiveness of the Islamic communication model in overcoming Pornography, Masturbation, and Orgasm (PMO) behavior among Communication Science students at the State Islamic University of North Sumatra. The urgency of this study arises because of the high prevalence of PMO among adolescents in Indonesia and the need for an approach that is integrated with Islamic values. The methodology involves the Analytic Hierarchy Process (AHP) and qualitative analysis to integrate Islamic communication principles and assess their effects on student behavior. The results of the study indicate that the Islamic communication model is effective in reducing PMO behavior, with the Interpersonal Psychotherapy Model (IPM) ranking the highest in effectiveness, followed by the Interpersonal Communication Model (ICM), Digital Campaign Model (DCM), Collaborative Group Discussion (CGD), Problem-based Learning (PL), and Islamic Lecture-based Instructional Model (ILIM). This approach reduces PMO incidents and supports students' emotional and spiritual growth. Based on these results, this study recommends a broader integration of the Islamic communication model in Islamic universities' curricula and extracurricular activities. It aims to enhance preventive education and support students in developing better psychosocial and spiritual health. This study also proposes further integration of Islamic communication models in the curriculum and extracurricular activities to develop a more holistic and in-depth preventive education. Thus, this study provides new insights into the effectiveness of value-based communication approaches in education and broadens the understanding of the adaptation of value-based education in addressing sensitive issues in higher education environments.